Cognitive Effects of Cranial Irradiation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The effects of cranial irradiation on neuropsychological test performance, 9 months after diagnosis of acute lymphoblastic leukemia (ALL), were evaluated in 74 children aged 3 to 6 years included in the Children's Cancer Group cooperative treatment trials.